In-situ characterization of microbial community in an A/O submerged membrane bioreactor with nitrogen removal - Sofia, A (Water science and technology : a journal of the International Association on Water Pollution Research, 2004)
The bacterial community involved in removing nitrogen from sewage and their preferred DO environment within an anoxic/oxic membrane bioreactor (A/O MBR) was investigated. A continuously operated laboratory-scale A/O MBR was maintained for 360 d. At a sludge age of 150 d and a C/N ratio of 3.5, the system was capable of removing 88% of the influent nitrogen from raw wastewater through typical nitrogen removal transformations (i.e. aerobic ammonia oxidation and anoxic nitrate reduction). Characterization of the A/O MBR bacterial community was carried out using fluorescence in situ hybridization (FISH) techniques. FISH results further showed that Nitrosospira spp. and Nitrospira spp. were the predominant groups of ammonia and nitrite oxidizing group, respectively. They constituted up to 11% and 6% of eubacteria at DO below 0.05 mg/l (low DO), respectively, and about 14% and 9% of eubacteria at DO between 2-5 mg/l (sufficient DO), respectively, indicating preference of nitrifiers for a higher DO environment. Generally low counts of the genus Paracoccus were detected while negative results were observed for Paracoccus denitrificans, Alcaligenes spp, and Pseudomonas stutzeri under the low and sufficient DO environments. The overall results indicate that Nitrosospira spp., Nitrospira spp. and members of Paracoccus spp. can be metabolically functional in nitrogen removal in the laboratory-scale A/O MBR system